Flexible memristor‐based LUC and its network integration for Boolean logic implementation. Issue 2 (19th March 2019) - Dong, Zhekang; He, Yufei; Hu, Xiaofang; Qi, Donglian; Duan, Shukai
Abstract : Memristor is a nanoscale electronic element with variable resistance that depends on the amount and direction of the charge passing through it. As a promising candidate, this memristive element opens up a new approach for the implementation of Boolean logic operations. In this study, a flexible logic unit circuit (LUC) based on a practical memristor model is proposed, which is able to perform the AND, OR, NOT, NOR, and NAND gate operations by different switch settings. Unlike existing memristor‐based logic implementation, the initialisation is not necessary for the proposed method, and the total delay can be effectively reduced, especially for time‐sequence inputs. Furthermore, the concept of the memristor‐based logic network is developed by multiple memristor‐based LUCs connected in series and parallel. The circuit simulation demonstrates that the presented logic network is capable of realising multi‐input–multi‐output logic operations with compact structure, high efficiency, and sufficient accuracy.